2010
DOI: 10.1002/hep.23803
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study on the natural history of serum hepatitis B surface antigen changes in chronic hepatitis B

Abstract: HBsAg remained stable in HBeAg-positive patients and tended to reduce slowly in HBeAg-negative patients. Reduction of HBsAg for >1 log IU/mL could reflect improved immune control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

25
193
3
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 228 publications
(226 citation statements)
references
References 30 publications
25
193
3
5
Order By: Relevance
“…Previous reports have suggested that HBsAg may reflect the content of intrahepatic HBV DNA and/or cccDNA, which serve as an intracellular template for viral RNA transcription, and it has been proposed as a surrogate marker for HBV-infected hepatocytes (58)(59)(60). However, other studies using the same HBsAg quantification platform could not confirm the association between HBsAg levels and cccDNA or intrahepatic HBV DNA in HBeAg ( À ) hepatitis B (61)(62)(63).…”
Section: Hbsag: Controversiesmentioning
confidence: 98%
“…Previous reports have suggested that HBsAg may reflect the content of intrahepatic HBV DNA and/or cccDNA, which serve as an intracellular template for viral RNA transcription, and it has been proposed as a surrogate marker for HBV-infected hepatocytes (58)(59)(60). However, other studies using the same HBsAg quantification platform could not confirm the association between HBsAg levels and cccDNA or intrahepatic HBV DNA in HBeAg ( À ) hepatitis B (61)(62)(63).…”
Section: Hbsag: Controversiesmentioning
confidence: 98%
“…The relative lack of relationship between HBsAg level and disease activity might reflect an uncoupling of HBV DNA and HBsAg production in the HBeAg-negative phase. In line with natural history studies, a reduction in HBsAg is probably reflecting a stepping up of immune clearance [8], which is a logical predictor of response to peginterferon therapy in HBeAg-negative patients.…”
mentioning
confidence: 62%
“…In a previous report among 19 HBeAg-negative patients with active disease (elevated ALT and/or HBV DNA [10,000 copies/ml), the HBsAg level could range from 1.57 to 3.85 log IU/ml [14]. In another case series, the range of the HBsAg level among 46 HBeAg-negative patients with elevated ALT varied from -0.42 to 4.09 log IU/ml [8]. The relative lack of relationship between HBsAg level and disease activity might reflect an uncoupling of HBV DNA and HBsAg production in the HBeAg-negative phase.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Recent studies have also shown the important role of HBsAg quantification in the natural history of CHB. HBsAg levels evolve along with the natural courses of CHB [7]. The HBsAg level is highest in the IT phase and starts to decline from the entry of the IC phase toward an LR phase, unless reactivation of HBV occurs.…”
mentioning
confidence: 99%